Self automated flood protection floating gate / Nur Farhada Johar Ariffin and Dzulkarnaen Ismail - Ariffin, Nur Farhada Johar; Dzulkarnaen Ismail, Dzulkarnaen (2023)
This research study aims to investigate and evaluate the effectiveness of an innovative flood gate, namely Self-Automated Flood Protection Floating Gate. Self-Automated Flood Protection Floating Gate is as a solution to enhance flood resilience in Malaysia. The frequent occurrence of floods in Malaysia, exacerbated by monsoon seasons and human-induced factors, has posed significant challenges to public safety, infrastructure, and economy. This study presents a comprehensive examination of the flood situation in Malaysia, explores innovative approaches to mitigate flood damage, and focuses on the development and assessment of the Self-Automated Flood Protection Floating Gate. The flood defence system is unique and effective which helps to protect people and property from inland waterway floods caused by heavy rainfall.